2011
DOI: 10.21608/jpp.2011.85774
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Behavior of Yield and Quality Traits in Sweet Melon Esmalawi Variety (Cucumis Melon –Var Agyptiacus)

Abstract: The highly polymorphic in sweet melon for many commercial traits providing seemingly endless possibilities for genetic improvement. The main objective of current study was to estimate of genetic behavior and obtain the genetic parameters of sweet melon advanced lines (Cucumis melo L. var. aegyptiacus). Eight inbred lines were developed from previous study using a pedigree selection method. The selected inbred lines were crossed according to factorial mating design generated 16 crosses. The additive genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…for days to female flower anthesis gave the best values (lowest values) over the all studied crosses for earliness fruits in the both seasons. These results are in confirmatory with those suggested by many workers found also significant differences among cucurbits regarding flowering and earliness traits among them, El-Gendy (1999), Ercan and Kurum (2003), Gabr (2003), Sadek (2003), Abdein (2005), Refai and Mohamed (2009), Ghobary and Ibrahim (2010), Moualla et al (2011), Shamloul and Askar (2011), Jahan et al (2012), Mohan et al (2012), El-Adl et al (2014), El-Gazzar et al (2015), Nada (2015), El-Shoura and Abed (2018) and Elias et al (2020).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…for days to female flower anthesis gave the best values (lowest values) over the all studied crosses for earliness fruits in the both seasons. These results are in confirmatory with those suggested by many workers found also significant differences among cucurbits regarding flowering and earliness traits among them, El-Gendy (1999), Ercan and Kurum (2003), Gabr (2003), Sadek (2003), Abdein (2005), Refai and Mohamed (2009), Ghobary and Ibrahim (2010), Moualla et al (2011), Shamloul and Askar (2011), Jahan et al (2012), Mohan et al (2012), El-Adl et al (2014), El-Gazzar et al (2015), Nada (2015), El-Shoura and Abed (2018) and Elias et al (2020).…”
Section: Resultssupporting
confidence: 91%
“…Mohan et al (2012) showed that there were significant differences among the genotypes of squash and cucurbits in fruit characteristics. Similar results were reported by, El-Gendy (1999), Abd El-Hadi et al (2001), El-Lithy (2002), Ercan and Kurum (2003), Gabr (2003), Sadek (2003), Abdein (2005), Refai et al (2009), Ghobary and Ibrahim (2010), Shamloul and Askar (2011), Jahan et al (2012), Omran (2012), El-Gazzar et al (2015), Habiba et al (2015), Nada (2015) and Elias et al (2020). *,** Significant and highly significant at 0.05 and 0.01 levels of probability, respectively.…”
Section: Concerning Squash Parents Data Presented Insupporting
confidence: 83%
See 1 more Smart Citation
“…In addition it had the best value for sex ratio (1.82) which mean expected high number of fruits and yield per plant. Many workers found also significant differences among squash regarding flowering and earliness traits among them, El-Gendy (1999), Ercan and Kurum (2003), Gabr (2003), Sadek (2003), Abdein (2005), Refai and Mohamed (2009), Ghobary and Ibrahim (2010), Moualla et al (2011), Shamloul and Askar (2011), Mohan et al (2012), Jahan et al (2012), El-Adl et al (2014).…”
Section: Flowering Traitsmentioning
confidence: 99%
“…As well as, the values of crosses ranged from 15.68 (P 1 xP 3 ) to 20.16 mg/100g (P 2 xP 3 , P 3 xP 1 ) for ascorbic acid content, 4.19 (P 2 xP 3 ) to 5.95% (P 1 xP 2 ) for total soluble solids, 5.79 (P 2 xP 3 ) to 7.00 % (P 1 xP 2 ) for dry weight of fruit, 11.40 (P 1 xP 2 ) to 13.00 (P 3 xP 2 ) for fruit number per plant and 1.12 (P 1 xP 2 ) to 1.32 kg (P 3 xP 2 ) for fruit yield per plant. Many investigators, El-Gazzar (1981), El-Gendy (1999), Abd El-Hadi et al (2001), El-Lithy (2002), Gabr (2003), Sadek (2003), Abdein (2005), Refai and Mohamed (2009), Ghobary and Ibrahim (2010), Shamloul and Askar (2011), Moualla et al (2011), Feyzian et al (2009), Omran et al (2012), Jahan et al (2012) and Mohan et al (2012) found highly significant differences among squash genotypes for these traits.…”
Section: Yield and Its Componentmentioning
confidence: 99%